Free fatty acids induce the demethylation of the fructose 1, 6-biphosphatase 2 gene promoter and potentiate its expression in hepatocytes. Issue 9 (16th April 2021) - Wang, Lujing; Liu, Min; Wu, Yucui; Li, Xingan; Yin, Fei; Yin, Li; Liu, Jianhui
Abstract : Free fatty acids induce the development of obesity by mediating the demethylation of fructose 1, 6-biphosphatase 2 gene promoters. Abstract : Obesity is a serious health issue as it is a social burden and the main risk factor for other metabolic diseases. Increasing evidence indicates that a high-fat diet (HFD) is the key factor for the development of obesity, but the key genes and their associated molecular mechanisms are still not fully understood. In this study, we performed integrated bioinformatic analysis and identified that fructose-1, 6 biphosphatase 2 (FBP2) was involved in free fatty acids (FFAs)-induced lipid droplet accumulation in hepatocytes and HFD-induced obesity in mice. Our data showed that palmitate (PA) and oleic acid (OA) induced the expression of FBP2 in time- and dose-dependent manners, and accelerated the development of lipid droplets in LO2 human normal liver cells. In HFD-fed C57BL/6 mice, accompanied by insulin resistance and lipid droplet accumulation, the mRNA and protein levels of FBP2 in the livers also increased significantly. The results from the methylation sequencing PCR (MSP) and bisulfite specific PCR (BSP) indicated that PA/OA induced the demethylation of the FBP2 gene promoter in LO2 cells. Moreover, betaine, a methyl donor, attenuated the expression of the FBP2 gene, the accumulation of lipid droplets, and the expression of perilipin-2, a biomarker of lipid droplets, in LO2 cells. All these findings revealed that FBP2 might be involved in HFD-induced obesity, and it is of interest to investigate the role of FBP2 in the treatment and prevention of obesity and its associated complications.